2016
DOI: 10.1016/j.prosdent.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Dental health professional recommendation and consumer habits in denture cleansing

Abstract: DHCP recommendations and denture wearer habits are diverse, with no consensus on the most appropriate denture cleaning methods. This reflects a lack of clear, systematic evidence upon which to base recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 16 publications
2
76
0
13
Order By: Relevance
“…Bu amaçla, çoğunlukla diĢ macunu ile fırçalama veya sabun ile yıkayarak temizleme yöntemleri kullanılmak-tadırlar. 23 Konu ile ilgili yapılan çalıĢmalarda ise diĢ macunu ve/veya genel temizlikte kullanılan çeĢitli sabun veya temizleyicilerin içeriğindeki aĢındırıcı madde miktarının hareketli protez kaidesine zararlı etkileri olduğu bildirilmiĢtir. 24,25 Hareketli protezlerin temizliğinde protez temizleme tabletlerinin kullanılması yaygın olarak önerilmek-tedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu amaçla, çoğunlukla diĢ macunu ile fırçalama veya sabun ile yıkayarak temizleme yöntemleri kullanılmak-tadırlar. 23 Konu ile ilgili yapılan çalıĢmalarda ise diĢ macunu ve/veya genel temizlikte kullanılan çeĢitli sabun veya temizleyicilerin içeriğindeki aĢındırıcı madde miktarının hareketli protez kaidesine zararlı etkileri olduğu bildirilmiĢtir. 24,25 Hareketli protezlerin temizliğinde protez temizleme tabletlerinin kullanılması yaygın olarak önerilmek-tedir.…”
Section: Discussionunclassified
“…Temizleme tabletleri içerdikleri hidrojen peroksit, alkalen peroksit, perasetik asit ve radikal oksijenler ile antimikrobiyal etki, sürfaktanlar ile de temizleme etkisi gösterirler ve genel olarak aĢındırıcı madde içermez-ler. 23 Su içerisinde çözünmüĢ olan alkalin veya hidrojen peroksitler efervesan aktivite göstererek protez kaidesi ile artık debrislerin arasındaki bağlanmayı çö-zerler. Bu aktivite polimer yapının organik matriksinde çözünme etkisi gösterir.…”
Section: Discussionunclassified
“…Furthermore, denture wearers fear that the esthetic problems of denture malodor and staining may reveal denture wearing to others. 15 A number of studies have reported various methods employed by denture wearers to clean dentures. These methods range from the simplest method being brushing with water and toothpaste which is considered routine to complex methods, such as use of chemical solutions and tablets.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of oral hygiene for patients with partial removable dental prostheses (PRDP) is a challenge, as many patients have a poor understanding of the most appropriate methods of maintaining hygiene. In many cases, patients use techniques and materials that may damage their prostheses …”
mentioning
confidence: 99%
“…Sodium hypochlorite and alkaline peroxides are the main chemical agents used to cleanse prostheses through immersion . These solutions may be used alone or in combination with mechanical methods.…”
mentioning
confidence: 99%